Mining the EU Global Strategy of 2016 - Szoszkiewicz, Łukasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
This study proposes to apply an automated lexical analysis to the European Security Strategy of 2003, entitled “A Secure Europe in a Better World”, and the European Union Global Strategy of 2016, entitled “Shared Vision, Common Acton: A Stronger Europe”. The findings are not limited to supporting the predominant interpretations of scholars and experts, but aim at exploring the usefulness of text mining techniques in the interpretation of EU documents. Furthermore, the conclusions drawn from the lexical analysis are discussed in the light of complex systems theory, which may be beneficial for the proper understanding of the concept of resilience (mainly its multidimensional nature) and its subsequent operationalization. The last part of the paper includes an in-depth analysis of the EU rhetoric on the UN fora (period: 2014–2019) regarding the concept of resilience, in particular its linkages with human rights.